Proses Editing Video konten pada Adobe Premier Pro di TV9 Nusantara Surabaya - Khofifah Nur Laila; Siti Mahmudah Yanti (An-Nashiha: Journal of Broadcasting and Islamic Comunication Studies, 2022)
This internship report discusses the process of editing video content using Adobe Premiere Pro at TV9 Nusantara Surabaya. The aim of this report is to provide information about the video editing process carried out at TV9 Nusantara Surabaya using Adobe Premiere Pro software. The methods used in this research are observation, interviews, and documentation. The results of this research show that the video editing process at TV9 Nusantara Surabaya using Adobe Premiere Pro involves several stages, including importing files, project settings, clip cutting, adding effects, and project completion. Additionally, this report also discusses the role and responsibilities of a video editor at TV9 Nusantara Surabaya in the video editing process. It is hoped that this report can be a reference for broadcasting students who want to learn about the video editing process at a television station.